(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Russianzi W, Anwar R, Triwidodo H. 2021. Biostatistics of fall armyworm Spodoptera frugiperda in maize plants in Bogor, West Java, Indonesia. Biodiversitas 22: 3463-3469. Fall Armyworm (FAW) Spodoptera frugiperda (J.E. Smith) is an invasive species that has become important pest of maize in Indonesia since 2019. This research was aimed to study the biology and demographic statistics of FAW in maize at Bogor. Daily observations of 132 FAW individuals from egg to death were carried out as the basis for compiling biology and life table. The demographic statistics of FAW were calculated using the Jackknife approach from the basic life table data. ImagoFAW actives at night. Mating activity occurs between 06.00 pm – 04.00 am, while egg-laying activity occurs between 06.00 pm-10.00 pm. Most hatching occurs between 00.00 am - 02.00 am. FAW has 6 larvae instars and there is no difference in stage between larvae that develop into male and female, which is around 15 days. The male pupae stage was longer than the female pupae, 8.78 ± 0.12 days and 7.81 ± 0.15 days. Male and female imagoes have the same life cycle, which is about 10 days. The life cycle of FAW was 32.26 ± 0.41 days, with a preoviposition period of 2.56 ± 0.45 days. Fecundity of FAW reaches 1012.62 ± 99.12 eggs per female imago. The population of FAW in Bogor has an intrinsic growth rate of 0.154 ± 0.001 individuals/day, with gross reproduction rate of 0.154 ± 0.001 individuals per generation, and net reproduction rate of 104.781 ± 0.155 individuals per imago per generation and a generation time of 30.114 ± 0.002 days.